Laboratory study of the nutrient release rate for vinasse on sandy soil and three coastal clay soils of Guyana - Clairmont Clementson; Lalita Gopaul (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Vinasse is produced in large quantities as a by-product from bioethanol production. To ensure environmental sustainability, a beneficial use was sought. Previous study showed that short-term crops grown with vinasse-amended soil provided higher yield than crops treated with chemical NPK (15:15:15) fertilizer. To understand this phenomenon, this study sought to establish the nutrient release rates of vinasse in the agricultural soils of Guyana. Methods Soils representative of the three most common and one futuristic agricultural land in Guyana were fertilized with vinasse, then watered as with normal course of plant growth of cash-crops for twelve weeks. The soil was sampled periodically, and the soil nutrients were determined. Results The nutrient availability from the application of vinasse as a soil amendment was greater for the clay soils than the sandy soil. EC was high while there was high availability of N, Ca, Mg, Fe and Mn during the 6-12th week. There was no discernable trend for tiwiwid sand. Conclusion In this laboratory study, high nutrient availability was observed in weeks 6-12 for the three clay soils studied. This period is the fruit and foliage growth phase for most short-term crops; hence, this suggests that vinasse is a good soil amendment for short-term crops in these soils. Vinasse did not improve the fertility of sandy soils; hence, it would be unsuitable as a fertilizer source in the Intermediate Savannahs of Guyana. Further studies should be done to fully determine the soil nutrient dynamics and the nutrient uptake.